2015
DOI: 10.3892/ol.2015.3629
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Livin shRNA on the response to cisplatin in HepG2 cells

Abstract: Abstract. Hepatocellular carcinoma is a lethal malignancy with poor prognosis, partially due to tumor metastasis, recurrence and resistance to chemo-or radio-therapy. Cisplatin can inhibit cancer cell DNA replication, and is widely used in the clinical treatment of tumors. The present study aimed to generate eukaryotic expression vectors for Livin shRNA and to examine the effects of Livin shRNA on the chemosensitivity of HepG2 hepatocellular carcinoma cells. Eukaryotic expression vectors for Livin shRNA (pSD11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, in the present study, we investigated the role of Livin in determining susceptibility to commonly used chemotherapeutic drugs, such as docetaxel, cisplatin and 5-FU, in human HNSCC cell lines. Although several studies have described that Livin contribute to the resistance of various chemotherapeutic drugs including cisplatin in various cancers (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), the present study is the first to demonstrate the correlation between Livin and chemoresistance in human HNSCC.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, in the present study, we investigated the role of Livin in determining susceptibility to commonly used chemotherapeutic drugs, such as docetaxel, cisplatin and 5-FU, in human HNSCC cell lines. Although several studies have described that Livin contribute to the resistance of various chemotherapeutic drugs including cisplatin in various cancers (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), the present study is the first to demonstrate the correlation between Livin and chemoresistance in human HNSCC.…”
Section: Introductionmentioning
confidence: 81%
“…Livin, a recently discovered IAP, is composed of a single BIR domain and a RING motif (9). Livin has been implicated in chemoresistance in various cancers (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). It has been reported to play a role in resistance to cisplatin in bladder cancer, renal carcinoma, gastic cancer, hepatocellular carcinoma, lung adenocarcinoma/ non-small cell carcinoma, osteosarcoma, colon cancer and ovarian carcinoma (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)31).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, silencing of livin reduced drug resistance to chemotherapy in glioblastoma, melanoma, and lung cancer [121314]. In addition, several studies have reported a synergetic anticancer effect when silencing of the livin gene is combined with chemotherapy [1516171819]. …”
Section: Discussionmentioning
confidence: 99%
“…In our assessment of outcome stability by sensitivity analyses, when a single study was removed, there were no significant changes of pooled OR, indicating that the results were consolidated. Significant association between Livin expression and lung cancer prognosis may be attributed to the binding between the BIR domain of Livin and caspase-3, 7 and 9, a process which inhibits caspase activity and blocks the apoptosis signal transduction of tumor cells ( 48 ). Alternatively, Livin may bind TAB1 to mediate the activation of JNK1 through TAB1 activation, a process which inhibits cell apoptosis ( 49 ) and subsequently causes tumor cell to metastasis and invasiveness.…”
Section: Discussionmentioning
confidence: 99%